Performances of the Online Self for Networked Audiences: An Introduction to the Special Issue. (January 2018) - Mishra, Smeeta; Ismail, Amani
Social media affordances enable us to construct multi-faceted online identities and personal brands that we use to engage and interact with audiences—defined and ambiguous, intended and unintended. There is a need to examine such online identities and associated micro-celebrity practices by users who appeal to multiple audiences through the strategic use of online spaces. In this special issue, we explore performances of our digital selves and the role played by active and interactive audiences in meaning-making within complex socio-political contexts while simultaneously attempting to understand varied positions of media refusal and enactments of digital media resistance.